Over Wańkowicz’s Coffin. The Polish People’s Republic and the Censorship of the Death and Funeral of the "Hubalczycy" (Hubal Partisans) Author - Bednarczuk, Monika (Porównania, 2025)
Melchior Wańkowicz returned to communist Poland in 1958, but his relations with the authorities were complicated since he was determined to maintain his independence. Since he enjoyed great popularity and was held in high esteem by various groups, his death and funeral provoked lively reactions from the press. Yet the numerous contributions, enthusiastic in their praise of Wańkowicz, incited discontent in the regime and, just three days after the writer’s funeral, a ban was issued on publications other than brief notes on the deceased. Although this instruction for censors was soon amended, several important texts were not permitted to be published. The article examines censoring practices between September and December 1974, building on documents from the Archives of Modern Records in Warsaw and the collection of the Main Office for the Control of the Press, Publications and Public Performances, and indicates the importance the authorities attached to the public discourse about Wańkowicz.